AGE AND GENDER PREDILECTION OF MESIODENS- A RETROSPECTIVE STUDY - A, Swetaa; S, Gheena; P, Jessy (International Journal of Psychosocial Rehabilitation, 2019)
Mesiodens is a supernumerary tooth which is placed in the midline between two central incisors or the position may change according to the individuals. Supernumerary teeth are a developmental disturbance occurring during odontogenesis resulting in the formation of the teeth in the excess of normal numbers. The aim of the study is to assess age and gender predilection of mesiodens among the general population. Retrospective analysis of all cases with a diagnosis of mesiodens. A total of 61 case sheets were reviewed from patient records. Tabulated in excel sheet. Imported to SPSS Version 20.O. Descriptive analyses were reported. The p value is not significant, in spite of the association presence of mesiodens in male population compared to female, hence the study should be done with a larger sample size.